The risk factors of fall among community - dwelling elderly in Air Itam, Penang - Ghous, Assillah Fatin Mohamad (Universiti Sains Malaysia, 2013)
Fall is defined as unintentionally coming to the ground or some lower level than that or from slipping, tripping or stumbling as a consequence of sustaining a violent blow, loss of conscious or sudden onset of paralysis as in stroke or epileptic seizure. Fall among elderly often related to accidents associated with the interaction between identifiable environmental hazards and increased individual susceptibility to hazards from accumulated effects of age and diseases. To identify the risk factors of fall among community-dwelling elderly in Air Itam, Penang. A cross-sectional survey using a set of self-administered questionnaire from the combination of Fall Risk Assessment Tool and Barthel’s Index Score on the risk factors. A total of 200 respondents were involved in this study. Data was analyzed using SPSS version 20.0 and Chi-Square test was used to analyze descriptive data. A total of 31% (n=62) reported to have experience fall. For cognitive status risk factor it was found that 79% of fallers have impaired cognitive status while 70% of fallers are psychologically impaired. P value less than 0.05 for the following items which reflect physical capability are the ability to shower, toileting, dressing, transfer, mobility and ability to climb stairs. There is also significant difference between incontinence and fall which reported 69.6% of fallers are within bowel incontinence whereas 63.3% of fallers are within urinary incontinence. Nutritional status, poor orientation to environment and poor eye sights and the risk of fall showed significant difference as the p < 0.001. Higher percentage of fall was among women than men and risk for fall increases with age. Evidently, with the percentage of 67.7% of fallers are women and 46.6% in the age group of 70-74 years old. The predisposed risk factors identified are age, gender poor physical performance, poor psychological status, poor cognitive function, deficit nutrition, impaired vision, bowel and urinary incontinence. Situational risk factors identified are locations such as toilet, kitchen and being outdoor increase the risk for fall.